Modeling the Health Impact and Cost-Effectiveness of a Combined Schoolgirl HPV Vaccination and Cervical Cancer Screening Program in Guangdong Province, China - Yating Huang; Dantao Zhang; Lihua Yin; Jianguo Zhao; Zhifeng Li; Jing Lu; Xiaoming Zhang; Chenggang Wu; Wei Wu (MDPI AG, 2024)
Low human papillomavirus (HPV) vaccine uptake is a key barrier to cervical cancer elimination. We aimed to evaluate the health impact and cost-effectiveness of introducing different HPV vaccines into immunization programs and scaling up the screening program in Guangdong. We used a dynamic compartmental model to estimate the impact of intervention strategies during 2023-2100. We implemented the incremental cost-effectiveness ratio (ICER) in costs per averted disability-adjusted life year (DALY) as an indicator to assess the effectiveness of the intervention. We used an age-standardized incidence of 4 cases per 100,000 women as the threshold for the elimination of cervical cancer. Compared with the status quo, scaling up cervical cancer screening coverage alone would prevent 215,000 (95% CI: 205,000 to 227,000) cervical cancer cases and 49,000 (95% CI: 48,000 to 52,000) deaths during 2023-2100. If the coverage of vaccination reached 90%, domestic two-dose 2vHPV vaccination would be more cost-effective than single-dose and two-dose 9vHPV vaccination. If Guangdong introduced domestic two-dose 2vHPV vaccination at 90% coverage for schoolgirls from 2023 and increased the screening coverage, cervical cancer would be eliminated by 2049 (95% CI 2047 to 2051). Introducing two doses of domestic 2vHPV vaccination for schoolgirls and expanding cervical cancer screening is estimated to be highly cost-effective to accelerate the elimination of cervical cancer in Guangdong.